FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN PERDARAHAN POSTPARTUM - Satriyandari, Yekti; Hariyati, Nena Riski (Universitas 'Aisyiyah Yogyakarta, 2017)
Abstract: This study was observational analytical study with case control method and retrospective approach. The samples were 80 mothers with 40 case samples and 40 control. The bivariate analysis technique used Chi-Square and the multivariate analysis used multiple logistic regression. The results of the bivariate analysis showed that there were three variables that have correlation with postpartum bleeding namely parity (p-value = 0.042, OR = 0.351), oxytocin drip (p-value = 0.002, OR = 8.222) and anemia (p-value = 0.016, OR = 4.846). The midwives are expected to be cautious in providing delivery care to the mothers who have risk factors for postpartum bleeding.Keywords: partum, risk factors bleeding , postpartum bleeding